PARADIPLOMASI PEMERINTAH PROVINSI BALI UNTUK SISTER PROVINCE BALI DENGAN HO CHI MINH DI BIDANG PARIWISATA - Dhita Kusuma Sabarno (UIN ALAUDDIN MAKASSAR, 2021)
Indonesia and Vietnam jointly carried out an increase in bilateral cooperation into a strategic partnership with tourism as one of the sectors to concentrate on. This is done, considering that currently the tourism sector is a sector that can be relied upon to improve people's welfare and national development for a country. The increasing number of tourist visits also made the two parties agree to pioneer a sister province cooperation between Bali-Ho Chi Minh in the tourism sector, considering that Bali and Ho Chi Minh themselves are tourism icons of each country. In the process, the Bali Provincial Government and the Vietnamese Government carried out various forms of activities as promotional efforts to joint assessments related to tourism for both parties. However, until now the process of implementing the Bali-Ho Chi Minh sister province cooperation has not continued, even the signing of the sister province cooperation agreement document planned for April 2020 has also been delayed due to the emergence of the covid-19 pandemic. However, currently the Bali Provincial Government is still intensively carrying out various efforts to revive the tourism sector and in its efforts to regain the trust of tourists to feel safe and comfortable traveling on the island of Bali. Keywords: Bilateral Cooperation, Paradiplomacy, Sister Province, Tourism